2007
DOI: 10.1080/14786410701371280
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of anti-inflammatory action of liquorice extract and glycyrrhizin

Abstract: The antiradical activity, protective effect against lipid peroxidation of liposomal membrane, and inhibitory effect on whole blood reactive oxygen species (ROS) liberation of Glycyrrhiza glabra crude extract and glycyrrhizin, its major compound, were assessed. The liquorice extract showed significant activity in all the three assay systems used in a dose dependent manner. It displayed remarkable reactivity with free stable 1,1'-diphenyl-2-picrylhydrazyl (DPPH) radical, inhibitory efficacy in peroxidatively dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…The major active component of licorice root is glycyrrhizin, an oleanane-type triterpene saponin which constitutes 2-24% of total dry weight (7). Glycyrrhizin is extensively reported to have several pharmacological activities including anti-inflammatory (8), immunomodulatory (9), antiulcer (10) and anti-tumorigenic activities (11,12). Glycyrrhizin also has antiviral activity against hepatitis B virus, HIV (13,14) and severe acute respiratory syndrome (SARS)-associated coronavirus (15).…”
Section: Introductionmentioning
confidence: 99%
“…The major active component of licorice root is glycyrrhizin, an oleanane-type triterpene saponin which constitutes 2-24% of total dry weight (7). Glycyrrhizin is extensively reported to have several pharmacological activities including anti-inflammatory (8), immunomodulatory (9), antiulcer (10) and anti-tumorigenic activities (11,12). Glycyrrhizin also has antiviral activity against hepatitis B virus, HIV (13,14) and severe acute respiratory syndrome (SARS)-associated coronavirus (15).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Glycyrrhizic acid, a major triterpene glycoside isolated from Glycyrrhiza glabra L. (liquorice) and G. uralensis, is the leading natural glycoside and the chief sweet-tasting constituent of these herbs. 26,27 Given the immunological findings obtained from the glycyrrhizic acid-treated pigs based on their H1N1 and H3N2 and considering that viral load for each virus type was not analysed in this study since only M gene was amplified, it can only be suggested that this preparation allows better resistance to the natural influenza viral challenge, compared to untreated pigs. …”
Section: Resultsmentioning
confidence: 99%
“…Its antiradical activity is reported to be responsible for its antiinflammatory action (Oh et al 2009;Rackova et al 2007;Yim et al 2007). However, the effect of AG against chemically induced depletion of DA and related biochemical parameters associated with signs and symptoms of PD and drug-induced extrapyramidal side effects or symptoms remains uncertain.…”
Section: Introductionmentioning
confidence: 95%